Correlation of Diffusion MRI Findings with Lesion Progression in Patients with Traumatic Intracerebral Hemorrhage - Erol, F. S.; Donmez, O.; Akgun, B.; Yildirim, H.; Kaplan, M. (Springer Heidelberg, 2014)
The aim of this study is to evaluate the association between lesion progression and the ischemic or edematous area that can develop around the hemorrhage in intraparenchymal hemorrhagic lesions originating after head trauma. Thirty patients with intracerebral hemorrhage due to head trauma of a mild or intermediate degree were evaluated in this study. Brain diffusion MRI examinations were performed in the first 6 h after trauma in all patients. In addition, a computerized cranial tomography (CCT) was performed upon admission (in the first hour), and at 24 and 48 h after admission. Patients with or without progression of the lesion were compared. The increase in the risk of progression of the lesion in patients with an ischemia/hemorrhage rate > 2 identified in the diffusion MRIs by evaluation of the hemorrhagic and the surrounding ischemic area, obtained in the first 6 h after trauma was found to be statistically significant. The possibility of progression was found to be very low when this rate was less than two. As a result of the study, the ischemic area was found to be proportionally larger in patients with progression compared to nonprogressing patients with traumatic intracerebral hemorrhage. The ischemia/hemorrhage rate in the diffusion MRI is thought to be an important parameter, beneficial to identify the risk of lesion progression.
Keywords: Head injury; Diffusion weighted MRI; Intracerebral hemorrhage; Progression